Noether Symmetries and Critical Exponents - Bozhkov, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
We show that all Lie point symmetries of various classes of nonlinear differential equations involving critical nonlinearities are variational/divergence symmetries.